2019
DOI: 10.1038/s41598-019-43412-2
|View full text |Cite
|
Sign up to set email alerts
|

Avenanthramide C from germinated oats exhibits anti-allergic inflammatory effects in mast cells

Abstract: Mast cells play a crucial role in allergic diseases via the release of inflammatory mediators, particularly histamine and pro-inflammatory cytokines. Avenanthramide (Avn) C, a polyphenol found mainly in oats, is known to exhibit various biological properties. In this study, we aimed to evaluate the effectiveness of Avn C from germinated oats against mast cell-mediated allergic inflammation. For the in vitro study, RBL-2H3, mouse bone marrow-derived mast cells and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 46 publications
1
18
0
1
Order By: Relevance
“…The germination of cereals has been used for centuries to soften kernel structure, decrease the content of antinutritive compounds, and to increase nutrient content and availability [17]. In this regard, an increase in the nutraceutical and phytochemical profile of oats could improve their biological activities, such as in the case of AVA-C (2c) from germinated oats, which exhibited antiallergic and anti-inflammatory activities [18]. Additionally, numerous trials and animal studies have demonstrated the bioavailability and bioaccessibility of polyphenolic compounds of oats, especially AVAs, and their association with an improved antioxidant status [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The germination of cereals has been used for centuries to soften kernel structure, decrease the content of antinutritive compounds, and to increase nutrient content and availability [17]. In this regard, an increase in the nutraceutical and phytochemical profile of oats could improve their biological activities, such as in the case of AVA-C (2c) from germinated oats, which exhibited antiallergic and anti-inflammatory activities [18]. Additionally, numerous trials and animal studies have demonstrated the bioavailability and bioaccessibility of polyphenolic compounds of oats, especially AVAs, and their association with an improved antioxidant status [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies show that Avn C exerts greater antioxidant activity than Avn A and B [ 16 , 17 , 18 , 38 , 39 ]. Dhakal et al [ 38 ] reported that Avn C from germinated oats exhibits anti-allergic and anti-inflammatory effects in mast cells, and Umugire et al [ 39 ] showed that Avn C exerts a strong protective effect on hearing loss caused by noise trauma. These results suggest Avn C as a promising candidate as a therapeutic for treating allergic diseases and hearing damage, given that Avn C can be provided through dietary products derived from oats.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also suggested that AVAs are potential inhibitors of the NFκB-mediated inflammatory response in select cell lines [92]. Avenanthramide C (AVC) from germinated oats were suggested as potential therapeutics for mast-cell-mediated allergic inflammation through the release of inflammatory mediators, histamine, and pro-inflammatory cytokines [93].…”
Section: Oats For Inflammationmentioning
confidence: 99%